2022
DOI: 10.3390/antibiotics11050664
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Approach in the Treatment of Descending Necrotizing Mediastinitis: Twenty-Year Single-Center Experience

Abstract: Descending necrotizing mediastinitis (DNM) is an acute, rare, severe condition with high mortality, but the optimal management protocol is still controversial. We retrospectively analyzed the results of multidisciplinary management in patients treated for DNM at our center over the last twenty years. Fifteen male patients, mean age 49.07 ± 14.92 years, were treated: 9 with cervico-pharyngeal etiopathogenesis, 3 peri-tonsillar/tonsillar, 2 odontogenic, 1 post-surgical; 6 with DNM type I, 6 with type IIA, and 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…Our results confirmed that the strategy suggested by De Palma et al [ 13 ] is effective: only transcervical drainage of the mediastinum by cervicotomy (performed in three patients) seemed to be a risk factor for postoperative complications in our series.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results confirmed that the strategy suggested by De Palma et al [ 13 ] is effective: only transcervical drainage of the mediastinum by cervicotomy (performed in three patients) seemed to be a risk factor for postoperative complications in our series.…”
Section: Discussionsupporting
confidence: 91%
“…Another point of strength in our results is the low rate of tracheotomy (16.9%) compared to the reported 60% of other series [ 13 ]. On this point, indeed, we agree with Kim [ 19 ], who considered tracheotomy not always necessary in DNM.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…The last two articles in our Special Issue focus on two topics of antimicrobial resistance. De Palma shares 20 years of experience in treating mediastinitis, a pathology with high morbidity, mortality and polymicrobial etiology [ 8 ].…”
mentioning
confidence: 99%